Unusual crystallization pathways revealed in six barium disilicate (BaSi2O5) glasses - Moulton, Benjamin J.A.; Silva, Laís D.; Sabino, Simone R.F.; Evaristo, Leonardo L.; Sampaio, David V.; Buchner, Silvio; Serbena, Francisco C.; Pizani, Paulo S.; Zanotto, Edgar D. (Ceramics International, 2023)
Due to the unusual crystallization of (nominally) stoichiometric BaSi2O5 (BS2) glass, which shows unexpected and diverse crystal phases, a series of six glasses with different chemicals and melting procedures were prepared in three laboratories and characterized before and after crystallization by differential scanning calorimetry, density measurements, X-ray diffraction, FTIR, and Raman spectroscopy. The aim of this study was to assess whether there is systematic behavior in the crystallization pathways in relation to precursor chemicals, impurities, and hydroxyl content of this glass. Small glass monoliths were treated at the first DSC crystallization peak and quenched to determine which phases formed in the early-stages of crystallization. The glass transition temperatures (Tg) divide these six glasses between those with a Tg near 690 °C versus those near 700 °C. The DSC peak crystallization temperatures varied even more; from 855 to 917 °C. In these six glasses, our results are best explained by a combination of metastable high-BaSi2O5 and Ba6Si10O26. Monotonic trends in crystallization show that the DSC signal from the Ba-rich phases increases as the Tg and the crystallization temperatures increase. The BS2 glasses with both the lowest Tg and lowest DSC crystallization temperatures show the most barium disilicate crystal. This leads to the conclusion that the metastable monoclinic high-BaSi2O5 is favored in these conditions. The small differences in glass synthesis conditions and chemicals used strongly influence the relative proportions of phases which crystallize and their kinetics. In-situ and ex-situ diffraction measurements confirm the conclusions above. The structural distinctions between the barium silicate crystals and the BS2 supercooled liquid, and the implications for the role of structural polymerization are discussed. We conclude that high-BaSi2O5 or Ba6Si10O26 are the predominant phases in the earliest stages of crystallization. This study highlights the extreme sensitivity of BS2 glass crystallization kinetics and pathways to minor differences in composition and synthesis conditions and explains the different conclusions reached by distinct authors that worked on the crystallization of BS2 glasses.
CRIS-Team Scopus Importer:2023-03-03
Keywords: Ba; Ba; Barium disilicate BaSi; DSC calorimetry; Homogeneous nucleation; Raman spectroscopy; Sanbornite; Silicate liquid; X-ray diffraction